2010
DOI: 10.1007/s00421-010-1763-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resistance training during hemodialysis on circulating cytokines: a randomized controlled trial

Abstract: The purpose of this study was to evaluate the effect of a 12-week intradialytic progressive resistance training (PRT) regimen on circulating pro- and anti-inflammatory cytokines. Forty-nine patients (62.6 ± 14.2 years) were recruited from the outpatient hemodialysis unit of the St. George Public Hospital, Sydney, Australia. Patients were randomized to: PRT + usual care (n = 24) or usual care control (n = 25). The PRT group performed two sets of 10 exercises at high intensity using free-weights, 3 times per wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 47 publications
(69 reference statements)
3
40
0
Order By: Relevance
“…[4][5][6] Strategies have been proposed to reverse the anorexia and, physical activity may be beneficial to increase appetite in CKD patients. 7 Studies about the effects of exercise on acyl-ghrelin and obestatin in CKD patients are scarce. A study of our group showed that 6 months of resistance exercise in hemodialysis (HD) patients was effective in reducing obestatin and increasing acyl-ghrelin levels.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Strategies have been proposed to reverse the anorexia and, physical activity may be beneficial to increase appetite in CKD patients. 7 Studies about the effects of exercise on acyl-ghrelin and obestatin in CKD patients are scarce. A study of our group showed that 6 months of resistance exercise in hemodialysis (HD) patients was effective in reducing obestatin and increasing acyl-ghrelin levels.…”
Section: Introductionmentioning
confidence: 99%
“…They did not observed any changes in the levels of TNF-a, IL-1b or C-reactive protein. 27,28 Nonetheless, there was an enhancement of functional capacity through aerobic exercise which was associated with the reduction of inflammatory state in CKD, and can be a secondary effect of rehabilitation programs. 29 Some limitations of this study should be mentioned: the relatively small sample size may lead to a statistical type I error; and the intensity of the exercise in EX session was performed using perceived exertion, which might affect adversely the control of the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Further, one RCT [49] noted no change in other pro-and anti-inflammatory cytokines, including IL-1b, IL-8, IL-10, and IL-12 secondary to 12 weeks of intradialytic PRT versus control.…”
Section: Cvd Risk Factorsmentioning
confidence: 99%
“…Intervention duration ranged from 8 weeks to 6 months. Four trials prescribed PRT outside of dialysis time [28,29,34,35,42,49], while 12 trials prescribed PRT during dialysis [26, 27, 29-32, 34, 35, 37-41, 48, 49] .…”
Section: Prt Interventionsmentioning
confidence: 99%